Visible spectrophotometric determination of Cefadroxil using ethyl acetoacetate and formaldehyde reagents - Susidarti, Ratna Asmah; Rianti, Andrih; Martono, Sudibyo (Indonesian Journal of Pharmacy, 2008)
Visible spectrophotometric method can be used to determine cefadroxil in the pharmaceutical dosage form. The reaction of cefadroxil with the condensation product of 2 mol ethyl acetoacetate and 1 mol formaldehyde in acidic condition (pH 3,5) at 45Â°C for 20 minutes yielded yellow product giving absorption at 367 nm. The concentration of Cefadroxil was calculated by using standard curve Y = 1.6063 X + 0.1634, r = 0.9932, p = 0,001 and Vxo = 9,7%. Determination of cefadroxil capsule â€Xâ€ (562.4 mg/capsule) showed that the concentration of cefadroxil observed is 490.5 mg/capsule (CV = 0.89%) and recovery value is 102.88% (CV = 0.67%). Key words: visible spectrophotometry, Cefadroxil, ethyl acetoacetate, formaldehyde